2019
DOI: 10.1002/ppap.201900133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field on the formation of Cu nanoparticles during magnetron sputtering in the gas aggregation cluster source

Abstract: Reliable production of nanoparticles (NPs) by magnetron sputtering in a gas aggregation source (GAS) is of great interest because of many potential applications. The size, shape, or structure of NPs can be tuned by the operational parameters of the GAS. In this study, fabrication of copper (Cu) NPs is investigated dependent on the magnetron magnetic field (MF)-a not much studied parameter. Decrease of the MF from 83 to 35 mT results in changes in the shape and size distribution of the NPs. MF also strongly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In the specific case of the formation of tungsten NPs, it was shown that the formation mechanisms and transport in between electrodes exhibit complex dynamics [17]. Since the mid-1990's, RF and DC magnetron sputtering in gas aggregation sources (MS-GAS) is commonly used to produce metal NPs [18][19][20][21][22][23][24][25][26]. In most cases, MS-GAS consists of a high-pressure chamber in which the magnetron discharge is located connected to a low pressure expansion chamber in which a beam of NP can be filtered and collected.…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of the formation of tungsten NPs, it was shown that the formation mechanisms and transport in between electrodes exhibit complex dynamics [17]. Since the mid-1990's, RF and DC magnetron sputtering in gas aggregation sources (MS-GAS) is commonly used to produce metal NPs [18][19][20][21][22][23][24][25][26]. In most cases, MS-GAS consists of a high-pressure chamber in which the magnetron discharge is located connected to a low pressure expansion chamber in which a beam of NP can be filtered and collected.…”
Section: Introductionmentioning
confidence: 99%
“…Using the very simple concept of linearly displacing the magnetic circuit with respect to the target (Fig. 2a), Vaidulych et al 71 managed to adjust the intensity of the magnetic field near the target surface (within the range 35–85 mT) and its corresponding efficiency in electromagnetic trapping of Cu nanoparticles nearby the target. As a result, when a sufficiently high flux of carrier gas was introduced in the condensation chamber, nanoparticles could escape more easily, with the resultant fivefold increase in deposition rate.…”
Section: Instrumentation Development Responsesmentioning
confidence: 99%
“…[11] Finally, the obtained clusters consist of tens and hundreds of thousands of metal atoms with a specific size distribution, number, shape, and crystalline structure. [9,[12][13][14][15] The species are subsequently filtered after the gas supersonic expansion stage that occurs at the exit of the nozzle opening. In the case of MNPs, in-flight self-assembly of clusters into chains after leaving the aggregation chamber has been reported.…”
Section: Introductionmentioning
confidence: 99%